An innovative maturity model to assess supply chain quality management - Cubo, Catarina (2021)
Purpose: This paper aims to present and discuss an innovative maturity model (MM) to assess supply chain quality management (SCQM). The SCQM MM can be used to guide organizations in the development and improvement of quality in their supply chains (SCs). Additionally, this paper intends to better understand that integration and its impacts on organizational performance. Design/methodology/approach: The proposed MM was developed based on an exhaustive literature review of the most relevant MMs developed in the areas of quality management, supply chain management and other relevant domains. Findings: The proposed MM consists of a matrix with 100 criteria organized in five organizational dimensions and five maturity levels, embracing the most relevant SC issues and describing a progressive path towards a state of full maturity. Originality/value: It is an innovative tool useful for both academic experts and practitioners to integrate quality management across the SC, thus promoting and improving organizational performance from an integrated and sustainable perspective.